2021
DOI: 10.3389/fonc.2021.539361
|View full text |Cite
|
Sign up to set email alerts
|

Intersecting Mechanisms of Hypoxia and Prostaglandin E2-Mediated Inflammation in the Comparative Biology of Oral Squamous Cell Carcinoma

Abstract: The importance of inflammation in the pathogenesis of cancer was first proposed by Rudolph Virchow over 150 years ago, and our understanding of its significance has grown over decades of biomedical research. The arachidonic acid pathway of inflammation, including cyclooxygenase (COX) enzymes, PGE2 synthase enzymes, prostaglandin E2 (PGE2) and PGE2 receptors has been extensively studied and has been associated with different diseases and different types of cancers, including oral squamous cell carcinoma (OSCC).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 227 publications
(260 reference statements)
0
6
0
Order By: Relevance
“…Transcriptional profiling showed that FOSCC is enriched with genes known to be upregulated in Human OSCC ( 34 ) suggesting conserved gene regulatory mechanisms. While these findings were predicted given the remarkable clinical, pathological, and genetic parallels between both tumors ( 9 , 37 , 60 62 ) they in no way confirm comparative origins or outcomes. The functional gene and canonical pathway enrichment analyses provided us further insight into the possible activation of several pathways that were seen in FOSCC that included EMT, hypoxia- and inflammation-related pathways ( 61 65 ), indicating the complementary value of gene expression analysis in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Transcriptional profiling showed that FOSCC is enriched with genes known to be upregulated in Human OSCC ( 34 ) suggesting conserved gene regulatory mechanisms. While these findings were predicted given the remarkable clinical, pathological, and genetic parallels between both tumors ( 9 , 37 , 60 62 ) they in no way confirm comparative origins or outcomes. The functional gene and canonical pathway enrichment analyses provided us further insight into the possible activation of several pathways that were seen in FOSCC that included EMT, hypoxia- and inflammation-related pathways ( 61 65 ), indicating the complementary value of gene expression analysis in this study.…”
Section: Discussionmentioning
confidence: 85%
“…Released from HNC and immune cells, vascular endothelial growth factor (VEGF) directly inhibits T cell development, including thymocyte maturation and differentiation [ 79 ], while IL-6 promotes platelet formation [ 80 ]. Further, PGE2 released from HNC cells can autocrinally induce the production of hypoxia-inducible factors and VEGF, which, subsequently, generates reactive oxygen species (ROS) from regulatory T cells, macrophages, and myeloid-derived suppressor cells within tumor tissue and in the peripheral blood [ 81 , 82 ]. The balance between the consumption and production of ROS determines T cell proliferation and function [ 81 ] and the initiation of thrombopoiesis from mature megakaryocytes in the bone marrow [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…During the inflammatory process, mediators such as cytokines, prostaglandins, and matrix metalloproteinases (MMP) are released and pro-inflammatory transcription factors are activated, such as NF-κB and the transducer and transcription activator signal 3 (STAT3), which play an important role in suppressing apoptosis, proliferation, angiogenesis, invasion, and tumor metastasis. Some studies, in vivo and in vitro, have demonstrated the deregulation of COXs [ 6 ], STAT3 [ 62 ], EGFR [ 63 ], VEGF [ 64 ], and CD147 [ 65 ] in FOSCC samples.…”
Section: Discussionmentioning
confidence: 99%